Development and status of moral education research: Visual analysis based on knowledge graph - Chen, Jingying; Liu, Yidan; Dai, Jian; Wang, Chengliang (Frontiers in Psychology, 2023)
Moral education is an educational process of the continuation, construction, and transformation of moral and social norms and is an important guarantee for the sustainable vitality of human morality. Using bibliometrics, this paper systematically quantifies the moral education research in K–12 and higher educational systems, analyzes 497 articles published in the Social Sciences Citation Index of Web of Science core collection from 2000 to 2022, and acquires the specific performance information in moral education from aspects of authors, journals, organizations, and countries, identifying the highly productive authors, organizations, and core journals (i.e., the Journal of Moral Education). A cluster analysis is used to show the knowledge structure, and an evolutionary analysis to present the macro-development trend of moral education. In this paper, the comprehensive description of the research topics on moral education clarifies the development model and disciplinary prospect of the moral education research and provides theoretical and practical support for the continuous development and application practice of the moral education research.